PENGARUH KEKUATAN MONITORING, MODAL, NPL DAN ASET TERHADAP MARGIN LABA PADA BPR KARESIDENAN PEKALONGAN - Supriyatun, Supriyatun; Kusumawardhani, Eny; Karyawati, Danik; Sumawan, Sumawan (UNPERBA, 2022)
This research aims to identify the influence of monitoring strength, capital, non-performing loans (NPL), and assets on net interest margin (NIM) in people's credit banks (BPR) in the Pekalongan area. The data analysis method used is multiple linear regression using secondary data obtained from the financial reports of BPRs and related institutions. The data used in this research uses secondary data from Conventional Rural Banks (BPR), which operates in the former Pekalongan Residency, Central Java for the 2018-2020 period, from Rural Bank Publication Financial Reports (LKP) which consist of balance sheets, Profit and Loss reports, administrative accounts and other information which is an integral part of the Published Financial Report, obtained from the Bank Indonesia directory www.bi.go.id. The research results show that monitoring strength, capital, and assets have a significant influence on NIM, while NPL does not have a significant influence. The implication of this research is the importance of managing monitoring power, capital, and assets effectively to increase NIM and the financial health of BPRs in the Pekalongan Resident area. It is hoped that this research can contribute to the understanding of the factors that influence BPR financial performance and become a consideration for related parties in making decisions regarding business strategy and banking policy.